The anatomy of government bond yields synchronization in the Eurozone - Claudio Barbieri; Mattia Guerini; Mauro Napoletano (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2021)
We investigate the synchronization of Eurozone's government bond yields at different maturities. For this purpose, we combine principal component analysis with random matrix theory. We find that synchronization depends upon yields maturity. Short-term yields are not synchronized. Medium- and long-term yields, instead, were highly synchronized early after the introduction of the Euro. Synchronization then decreased significantly during the Great Recession and the European Debt Crisis, to partially recover after 2015. We show the existence of a duality between our empirical results and portfolio theory and we point to divergence trades and flight-to-quality effects as a source of the self-sustained yield asynchronous dynamics. Our results envisage synchronization as a requirement for the smooth transmission of conventional monetary policy in the Eurozone.
Keywords: C38; E43; E58; 330; Synchronization; Bond Yields; Factor Models; Random Matrix Theory; Monetary policy